2020
DOI: 10.1590/1414-431x202010279
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of lung function in predicting distance covered in the 6-min walk test in obese Brazilian women

Abstract: Obesity affects the respiratory system through various mechanisms, including systemic inflammation and direct mechanical hindrance due to fat deposition in the chest and abdomen. In addition, changes in the neural control of respiration and increases in thoracic blood volume can promote abnormalities in lung function. Thus, determining relationships between the distance covered in the 6-min walk test (6MWT) and demographic and lung function variables may help us better understand the mechanisms involved in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(55 reference statements)
0
3
0
5
Order By: Relevance
“…Although Enright and Sherrill's equations have been used in clinical practice in subjects with different BMIs, the conversion factors in the formula are unreliable because these equations were originally validated for BMI <35 kg/m 2 [ 6 ]. Furthermore, their study excluded subjects with FEV 1 < 70% of the predicted value, although lung function is a major contributor to performance during the 6 MWT in obese people [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Enright and Sherrill's equations have been used in clinical practice in subjects with different BMIs, the conversion factors in the formula are unreliable because these equations were originally validated for BMI <35 kg/m 2 [ 6 ]. Furthermore, their study excluded subjects with FEV 1 < 70% of the predicted value, although lung function is a major contributor to performance during the 6 MWT in obese people [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although spirometry test results have been used in preoperative assessments of obese people, their relationship with the functional capacity of obese individuals is uncertain [9,10]. Considering the need to estimate cardiopulmonary function in the preoperative evaluation for bariatric surgery and to establish the surgical risk, knowing the influence of lung function measurements on the 6 MWD is important [1,[9][10][11][12]. us, we aimed to establish a reference value for the 6 MWD in obese Brazilian men in the preoperative period of bariatric surgery that considers the effect of lung function.…”
Section: Introductionmentioning
confidence: 99%
“…En trabajos realizados con la PC6M se ha informado de la limitación para caminar en poblaciones con obesidad mórbida (IMC > 40 kg/m 2 ) 12,[17][18][19][20] . Maniscalco et al lo reportaron en sujetos con IMC 42.1 (rango: 39-49 kg/m 2 ) que disminuyó a 31.9 (25-38 kg/m 2 ) a un año de realizado bandaje gástrico.…”
Section: Introductionunclassified
“…Larsson et al 17 reportaron en sujetos con IMC > 40 kg/m 2 una diferencia de 25 metros entre una primera y segunda PC6M y buena reproducibilidad (4.7%) evaluada por coeficiente de variación. Luchesa et al en mujeres 19 con IMC > 45 ± 8 kg/m 2 y hombres 20 48.1 ± 8.4, kg/m 2 , informaron que la disminución de la capacidad de caminar (hacer ejercicio) estaba relacionada con las alteraciones de la función pulmonar debido a la infiltración grasa de la caja torácica y abdomen que llevó a compresión pulmonar por el efecto mecánico restrictivo del diafragma y del movimiento de las costillas, lo que redujo la distensibilidad pulmonar.…”
Section: Introductionunclassified
“…Some studies [ 20 ] have shown that reference equations for the 6MWD, which were derived mainly from healthy, normal-weight populations, are not suitable for obese subjects and that specific reference equations for the 6MWD in obese subjects should be established. Although 6MWD reference equations derived from obese subjects of other ethnicities have been established [ 9 , 21 23 ], these equations may not be applicable to obese Chinese people. The lack of 6MWD reference equations for obese Chinese subjects limits the applicability of the 6MWT for obese patients and makes it difficult for clinicians who use the 6MWD.…”
Section: Introductionmentioning
confidence: 99%